Matrix analysis and applied linear algebra - Meyer, Carl (SIAM, 2000)
Linear equations - Rectangular systems and echelon forms - Matrix algebra - Vector spaces - Norms, inner products and orthogonality - Determinants - Eigenvalues and eigenvectors - Perron-Frobenius theory.